My promised land eaudiobook The triumph and tragedy of israel. - Shavit, Ari (Random House Audio, 2013)
NEW YORK TIMES BESTSELLER • A NEW YORK TIMES BOOK REVIEW AND ECONOMIST BEST BOOK OF THE YEAR “ A deeply reported, deeply personal history of Zionism and Israel that does something few books even attempt: It balances the strength and weakness, the idealism and the brutality, the hope and the horror, that has always been at Zionism’s heart.”—Ezra Klein, The New York Times Winner of the Natan Book Award, the National Jewish Book Award, and the Anisfield-Wolf Book Award Ari Shavit’s riveting work draws on historical documents, interviews, and private diaries and letters, as well as his own family’s story, to create a narrative larger than the sum of its parts: both personal and of profound historical dimension. As he examines the complexities and contradictions of the Israeli condition, Shavit asks difficult but important questions: Why did Israel come to be? How did it come to be? Can it survive?    Culminating with an analysis of the issues and threats that Israel is facing , My Promised Land uses the defining events of the past to shed new light on the present. Shavit’s analysis of Israeli history provides a landmark portrait of a small, vibrant country living on the edge, whose identity and presence play a crucial role in today’s global political landscape.